Project Report on Online Registration for Blood Donation - AKSHAY KABADI, HIREKOTRAIAH, SHARATH S L and RAVISH H S (2008)
INTERNAL GUIDE: UMESH KUMAR, MVJCE EXTERNAL GUIDE: NARAYAN, E2E SOLUTIONS LTD
Keywords: Online Registration for Blood Donation